Direct Quranic quotation methods in Kitāb Al-Kifāyah and Kitab Risalah Fi Bayan Hukm Al-Bay' Wa Al-Riba: A comparative study - Zurita, Mohd Yusoff; Noor Anida, Awang; Syed Mohd Hafiz, Syed Omar; Hasalnulddin, Mohd; Engku Ibrahim, Engku Wok Zin (2017)
The Quran has been revealed by Allah SWT as a primary source of Islamic law, followed by the Hadith, the Ijma’ and the Qiyas. Scholars of the past, including in Terengganu such as Shaykh Abdul Malik and Shaykh Abdul Qadir, have been known to use direct Quranic quotation methods in their manuscripts. The direct Quranic quotation methods in the Kitab al-Kifayah, for example, are likely to differ from the Kitab Risalah Hukm al-Bay’ Wa al-Riba. In this paper, the researchers studied the respective authors’ background and the direct Quranic quotation methods employed in their manuscripts. This histography study uses the documentation method to achieve the above-mentioned objective. This study finds that there are both similarities as well as differences in their direct Quranic quotation methods. They employed similar quotation techniques by not stating the name of the surah and its verses in their respective manuscripts. In contrast, however, Quranic verses in the Kitab al-Kifayah were used mainly to explain stories and/or metaphors found in the Quran, whereas the ones in Kitab Risalah were mainly used to contextualise arguments in fatawa-issuance. As a result, the number of Quranic verses used in the Kitab Risalah Hukm al-Bay’ are significantly higher than in the Kitab al-Kifāyah.